Tax Avoidance and Company Characteristics in Non-financial companies listed on the Indonesia Stock Exchange - Callista, Vania Aurea; Siahaan, Magda; Nauli, Theonino David (Economics Professional in Action (E-Profit), 2024)
This research aims to obtain empirical evidence regarding the effect of profitability, leverage, firm size, capital intensity, institutional ownership, board of directors’ size, audit committee, and sales growth on tax avoidance. The population of this research is non-financial companies that are consistently listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021. The number of research samples collected using the purposive sampling method is 450 data. This research uses the multiple regression method to determine the effect of independent variables on dependent variables. The results of this research stated that the variables of profitability, leverage, firm size, and audit committee affect tax avoidance, while the variables of capital intensity, institutional ownership, board of directors’ size, and sales growth do not affect tax avoidance.